Effective Methods Of Teaching A Foreign Language - Nafosat Yuldasheva (International Scientific and Current Research Conferences, 2020)
The article covers the analysis of innovative methods concerning teaching a foreign language for special purposes and the idea of effective teaching a language learner with the help of modern educational practice.